Optimizing irrigation scheduling for winter wheat production in the Hebei Plain using the AquaCrop model - XUAN Ziyu; ZHANG Xiaotao; DANG Hongkai; NIU Jun (Guan'gai paishui xuebao)
【Objective】Reducing groundwater use for irrigation has been a key mandate in the Hebei Plain to promote sustainable agriculture. Improving irrigation water use efficiency is therefore essential to achieving this goal. This study aims to develop a method to optimize irrigation scheduling for winter wheat in this region.【Method】A field experiment was conducted from October 2022 to June 2023 at a winter wheat field in Hengshui City, Hebei Province. Four irrigation schedules were compared: irrigating once (W1), twice (W2), three times (W3), and four times (W4) during the growing season. Experimental data were used to calibrate and validate the AquaCrop model. The calibrated parameters were then applied to optimize irrigation scheduling.【Result】The calibrated AquaCrop model accurately simulated canopy development, above-ground biomass, and soil moisture dynamics. The coefficient of determination (R2), root mean square error (RMSE), normalized RMSE (NRMSE), Nash-Sutcliffe efficiency (EF), and index of agreement (d) between the simulated and measured values all fell within acceptable ranges, with R2＞0.85, RMSE＜4.5, NRMSE＜12, EF＞0.8, and d＞0.9. The average error of the simulated grain yield was higher in 2021 than in 2022. Water use efficiency under the W3 treatment was 1.88 kg/m3 in 2021 and 2.35 kg/m3 in 2022.【Conclusion】Among the four irrigation schedules, W3 (irrigating three times) was the most effective in improving both grain yield and water use efficiency for winter wheat in the Hebei Plain. The calibrated AquaCrop model accurately simulated winter wheat growth and can be used to optimize irrigation scheduling and improve irrigation water use efficiency in this region and other areas with similar environments.